Caco-2 Intestinal Permeability Study of Phenyltetrahydroquinolinedione Derivative – TRPA₁ Antagonist - N. V. Pyatigorskaya; A. D. Kravchenko (Разработка и регистрация лекарственных средств, 2022)
Introduction. This work is devoted to the intestinal permeability study of 7-(2-chlorophenyl)-4-(4-methyl-1,3-thiazol-5-yl)-4,6,7,8-tetrahydroquinoline-2,5(1H,3H)-dione – innovative biologically active substance with TRPA1 antagonist activity. The phenyltetrahydroquinolinedione derivative is a promising analgesic and anti-inflammatory drug. To develop a dosage form of this new substance, it is necessary to study the mechanism and degree of its absorption.Aim. The aim of this work was to investigate the intestinal permeability of the phenyltetrahydroquinolinedione derivative using Caco-2 cell model and to compare experimental results with the in silico obtained values of the octanol/water partition coefficients.Materials and methods. The study of permeability was carried out from the apical membrane to the basolateral (A-B) and in the opposite direction (B-A). Ranitidine (low permeability), propranolol (high permeability) and rhodamine 123 (P-glycoprotein substrate) were used as control compounds. The concentration of the test compound was determined by UHPLC-MS/MS system consisting of a liquid chromatograph and a tandem mass spectrometer with a triple quadrupole and an electrospray ion source. The logP was calculated using the following resources: ChemDraw Professional 16.0, Molinspiration, ALOGPS 2.1.Results and discussion. The values of the apparent permeability (Papp) and efflux ratios of the test and control compounds were obtained. According to the results of the study, the following conclusions were made: the test compound has high permeability both in the forward direction from the apical to the basolateral cell membrane, and in the opposite direction (Papp > 10 × 10-6 cm/s). P-glycoprotein-mediated efflux activity was not observed (the efflux ratio was less than 2 units). The permeability did not depend on the test compound input concentration. The obtained experimental Papp values were correlated with the in silico obtained values of partition coefficients. The best correlation was obtained for milogP (Molinspiration) and ClogP (ChemDraw).Conclusion. Thus, the in vitro and in silico obtained data indicate that passive diffusion is the main mechanism of absorption of the test compound in the gastrointestinal tract.